2012
DOI: 10.4293/108680812x13462882736970
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laparoscopic Distal Pancreatectomy for Solid Pseudopapillary Tumor

Abstract: Results of this study suggest that laparoscopy may offer an alternative to open surgery in the treatment of solid pseudopapillary tumors of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…Additionally, we also found excellent long-term prognosis after complete surgical resection for SPPN with 5-yr OS rates of 96% 2791136. Hence, in addition to improving short-term perioperative outcomes with the performance of MIS in this group of patients,192021222324252627282930 further potential longer-term benefits associated with MIS such as improved wound cosmesis, decreased long-term wound complications such as paresthesia and chronic pain and decreased intra-abdominal adhesions could be especially important.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Additionally, we also found excellent long-term prognosis after complete surgical resection for SPPN with 5-yr OS rates of 96% 2791136. Hence, in addition to improving short-term perioperative outcomes with the performance of MIS in this group of patients,192021222324252627282930 further potential longer-term benefits associated with MIS such as improved wound cosmesis, decreased long-term wound complications such as paresthesia and chronic pain and decreased intra-abdominal adhesions could be especially important.…”
Section: Discussionmentioning
confidence: 52%
“…One of the first series of laparoscopic distal pancreatectomies for SPPN comprising 10 patients was published by Cavallini et al30 in 2011, which reported 40%, 20% and 0% postoperative morbidity, reoperation and perioperative mortality rates respectively. Since then, several institutions have published their experience with MIP for SPPN, all of which have consistently concluded that MIP is a safe and feasible approach in the management of SPPN 19212223242628. These studies however lack comparative analysis against SPPN managed via a conventional open approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El TSP constituye una neoplasia atípica debido a su comportamiento indolente habitualmente benigno pero con potencial maligno hasta en 15% de los casos 15 . Representa menos de 2% de todos los tumores pancreáticos y 10% a 15% de los tumores quísticos [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . En la IV Región el TSP se presentó en 13% de todos los pacientes sometidos a resecciones pancreáticas tumorales, esta alta incidencia se debe seguramente a un sesgo ocasionado por el pequeño número de pancreatectomías realizadas.…”
Section: Discussionunclassified
“…El tipo de resección depende de la localización del tumor, la localización más frecuente es la cola del páncreas (33% a 80%), seguida por la cabeza (32% a 67%), cuerpo (14% a 27%) y proceso uncinado (3%) 3,4,14,18 . Habitualmente se realizan pancreatectomías distales para los tumores de cuerpo y cola y pancreatoduodenectomías para los tumores de cabeza y cuello 1,4,10,12,19 . Aunque la enucleación de tumores pequeños ha sido descrita, esta no se recomienda debido a que los TSP presentan un patrón de crecimiento celular infiltrante al parénquima pancreático adyacente y a los tejidos circundantes 1 , tal y como se presentó en un paciente de esta serie.…”
Section: Discussionunclassified